An efficient algorithm for improving precision of multi-cell channel estimation systems - Marzook, Ali Kamil; A., Ismail; Mohd Ali, Borhanuddin; Sali, Aduwati; Khatun, Sabira (Elsevier, 2012)

(untitled)
A new multi-cell joint channel estimation technique for uplink TD-SCDMA system is proposed. The Channel impulse responses of the serving cell and the effective neighboring cell users will process jointly. The new technique adopts the singular value decomposition criterion to reduce the rank order of the system channel matrix. Depending on a limited number of the real parameters that need it to describe the channel matrix, the estimation process will be efficient and the reduced rank technique can significantly improve the channel estimation accuracy. Simulation results show clearly that the proposed reduced rank estimator can significantly improve the channel estimation accuracy for multi-cell networks under rank-deficient consideration. The mean square error (MSE) measure has shown the validity performance of the proposed estimator over the conventional estimators. In addition, the correlation coefficient measures of the reduced rank estimators have shown slightly the superiority of the proposed technique.